2007
DOI: 10.1007/bf03347409
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous ghrelin increases in adriamycin-induced heart failure rats

Abstract: Evidence has indicated that plasma ghrelin was elevated in chronic heart failure (CHF) patients with cachexia. The present report studied whether pathophysiologic increment of endogenous ghrelin levels was existed in the progression of adriamycin (ADR)-induced CHF, then the possible compensatory mechanism by which the changes were induced and the relationship between active ghrelin, cardiac function and energy reserve in heart failure (HF) rats were explored. Cardiac function, high energy phosphates (HEP) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Of note, desacyl ghrelin has been shown to cause a rapid and strong activation of ERK1/2 and Akt in rat cortical neuronal cells (10). Cardioprotection by ghrelin (acylated) against doxorubicin was later supported by in vivo evidence showing that endogenous ghrelin is increased during the progression of heart failure, and it was suggested to represent a compensatory protective response to maintain the cardiac function during doxorubicin-induced cardiomyopathy (60). To date, the therapeutic role of desacyl ghrelin in doxorubicin cardiotoxicity has not been demonstrated in vivo.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Of note, desacyl ghrelin has been shown to cause a rapid and strong activation of ERK1/2 and Akt in rat cortical neuronal cells (10). Cardioprotection by ghrelin (acylated) against doxorubicin was later supported by in vivo evidence showing that endogenous ghrelin is increased during the progression of heart failure, and it was suggested to represent a compensatory protective response to maintain the cardiac function during doxorubicin-induced cardiomyopathy (60). To date, the therapeutic role of desacyl ghrelin in doxorubicin cardiotoxicity has not been demonstrated in vivo.…”
mentioning
confidence: 80%
“…With regard to heart failure, ghrelin (acylated) has been shown to improve ventricular dysfunction and ameliorate ventricular remodeling and cardiac cachexia in rats with chronic heart failure induced by experimental ligation of the left coronary artery (38). Specifically for doxorubicin cardiotoxicity, there is in vivo evidence that the endogenous ghrelin (acylated) level is increased during the progression of heart failure induced by doxorubicin (60), leading to the suggestion that ghrelin (acylated) might contribute to a compensatory self-protective mechanism that is linked to antiapoptosis and antioxidative mechanisms and maintains cardiac function (60). Notably, the functional effects of desacyl ghrelin on cardiac disorders are relatively unidentified, although some in vitro data suggest the beneficial effects of desacyl ghrelin on doxorubicin cardiotoxicity by inhibiting cardiomyocyte cell death (2).…”
Section: Discussionmentioning
confidence: 99%
“…In rat models of isoproterenol ISO [43] -or adriamycin ADR [81] -induced myocardial injury, endogenous plasma ghrelin levels increased significantly, perhaps due to a compensatory, self-protective mechanism. Moreover, administration of exogenous ghrelin can protect against ISOinduced myocardial injury [43]; and in in vitro studies, ghrelin has shown to prevent against the cardio-toxicity of ADR [82].…”
Section: ) Ghrelin and Drug-induced Myocardial Injurymentioning
confidence: 99%
“…Growing of evidence shows that ghrelin decreases oxidative stress by enhancing anti-oxidant defense [351,352]. Endogenous ghrelin levels were increased during early stage of heart failure development to maintain myocardial energy balance and improve cardiac function as a compensatory effect, indicating ghrelin exerted anti-oxidative and anti-apoptotic effect through myocardial mitochondrial function [351].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous ghrelin levels were increased during early stage of heart failure development to maintain myocardial energy balance and improve cardiac function as a compensatory effect, indicating ghrelin exerted anti-oxidative and anti-apoptotic effect through myocardial mitochondrial function [351]. An in vitro study on hypoxic injury demonstrated that ghrelin administration reduced ROS content with increased Mn-SOD gene expression and activity via an AMPK-dependent pathway [352].…”
Section: Discussionmentioning
confidence: 99%